Experimental Study on the Damage of Bridge Pier under the Impact of Rockfall. (11th March 2021) - Sun, XinPo; Bi, YuZhang; Zhou, RuoYun; Zhao, HouZhen; Fu, Xian-Lei; Zhao, Pu; Jiang, Zhe-Yuan
Abstract : In this paper, a discussion is presented about the impact-induced damage suffered by bridge pier columns during rockfall events through model tests and impact force, column top displacement, stress-strain response, and other parameters in relation to the process of impact. On this basis, the following conclusions are drawn. Firstly, the impact force, as well as the displacement and strain of the column top, increases rapidly after taking a hit, while the displacement is reduced after reaching its maximum. Secondly, at the same falling height, the higher the impact position, the smaller the peak of impact force and the longer the attenuation period. Thirdly, at the same impact height, the impact energy, the displacement of the column top, and the peak of the impact force increase as the falling height of the pendulum ball is on the rise, but the attenuation period remains unchanged. Fourthly, the failure mode of column impacted by the swing ball conforms to shear-flexural failure. Fifthly, it is recommended to strengthen the preventative measures for those weak positions like 1/2 height and 1/4 height of bridge pier, so as to minimize the potential damage caused by rockfalls. Besides, a theoretical formula used to estimate the maximum impact force is proposed. Lastly, under the axial load of bridge deck, the performance of the pier in impact resistance under rockfall is better and the damage is less severe than in the experimental impact test. The axial load applied by the deck imposes some constraints on the pier, thus reducing concrete damage. The research results can contribute to the research on addressing the rockfall-bridge pier collision problem. The experimental research demonstrates its theoretical significance to engineering for the prevention of rockfall.